2001
DOI: 10.1046/j.1440-1614.2001.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Ageing in the New Millennium

Abstract: Our understanding of the functional and structural changes associated with both healthy and pathological ageing is rapidly gaining in sophistication and complexity. An awareness of the fundamental biological substrates underpinning the ageing process will allow improved insights into vulnerability to neuropsychiatric disease associated with advancing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 212 publications
(237 reference statements)
1
40
0
Order By: Relevance
“…This decrease is relatively diffuse and uniform in cerebral white matter but shows some regional differences in grey matter, with frontal and parietal cortex more affected than temporal and occipital cortex and with the striatum also affected [10][11][12][13]. Brain volume reductions increase from about 0.1-0.2%/year at age 30-50 years to 0.3-0.5%/year over the age of 70 years, in agreement with brain weight studies.…”
Section: Esirisupporting
confidence: 82%
“…This decrease is relatively diffuse and uniform in cerebral white matter but shows some regional differences in grey matter, with frontal and parietal cortex more affected than temporal and occipital cortex and with the striatum also affected [10][11][12][13]. Brain volume reductions increase from about 0.1-0.2%/year at age 30-50 years to 0.3-0.5%/year over the age of 70 years, in agreement with brain weight studies.…”
Section: Esirisupporting
confidence: 82%
“…Studies have shown, for example, that older age brings about declines in fluid intelligence (Berg, 2000;Carroll, 1993;Van Gerven et al, 2000), crystallized intelligence (Berg, 2000;Christensen, 2001;Meyer et al, 2001), processing speed (Berg, 2000;Deary, 2000;Troller and Valenzuela, 2001;Wood et al, 2005), working memory (Berg, 2000;Meyer et al, 2001;Troller and Valenzuela, 2001;Wood et al, 2005;Zacks et al, 2000), episodic memory (Burke and Mackay, 1997;Zacks et al, 2000), learning abilities (Albert, 1997;Rabbitt, 1997;Troller and Valenzuela, 2001), and the ability to filter out irrelevant information (Van Gerven et al, 2000;Zacks et al, 2000).…”
Section: Decline In Cognitive Abilitiesmentioning
confidence: 99%
“…Decreases in brain volume, cerebral metabolism, and blood flow have been found to occur with aging (Leenders et al, 1990; Marchal et al, 1992;D'Esposito et al, 1999;Buckner et al, 2000;Trollor and Valenzuela, 2001). However, it is highly unlikely that such age-related changes would systematically result in group differences that are regionally dissociated (e.g., decreased activation in the caudate and prefrontal cortex along with increased parietal activation in older adults relative to younger adults).…”
Section: Goldmanmentioning
confidence: 99%